Effect of Space Thermal Environment on Normal Operation of Space Reactor Power System SP-100 - HUANG Jinlu1, 2, WANG Chenglong1, , LIU Tiancai2, GUO Chunqiu2, TIAN Wenxi1, SU Guanghui1, QIU Suizheng1 (Yuanzineng kexue jishu)
The space reactor power is in the complicated space thermal environment during the launching from earth to orbit, which mainly includes direct irradiation from the sun, earth albedo and earth infrared irradiation. In this study, SP-100 core-Stirling space reactor power system was taken as the research object, and the Thermal Desktop’s SINDA/FLUINT with RadCAD module was used to carry out thermal analysis and calculation during in-orbit operation of space reactor power, so as to study the influence of space thermal environment on normal operation of space reactor power. According to the calculation model, design input and orbit parameters of the space reactor, the three-dimensional temperature field distribution and space heat flow distribution of the space reactor under different β angle, flight attitude and orbit altitude were obtained by setting four calculation conditions. Based on the difference of orbital plane β angle and orbital altitude of space reactor power supply, the hottest and coldest working conditions of power supply during orbit were determined and thermal analysis was carried out. The results show that the temperature of the SP-100 reactor power system changes periodically with time during full power operation in orbit. The temperature of the primary circuit lithium coolant at high temperature range changes little with the orbital period fluctuation, and there is almost no temperature difference, while the temperature of the secondary circuit lithium coolant at low temperature range changes greatly with the orbital period fluctuation, and the maximum temperature difference between the inlet and outlet ducts of the radiator is 25 K. The influence of space thermal environment on the temperature of space reactor power is also related to the orbital plane β angle, orbital altitude and orbital attitude of the space reactor power. Orbit attitude and orbit altitude have little influence on the normal operation of space reactor, while β angle has obvious influence. Launching a space reactor into orbit when the β angle is larger than the critical angle of total sunshine will be beneficial to the cold start-up process of the space reactor. Therefore, it is necessary to determine the orbit parameters and attitude of the space reactor power to ensure that all components of the space reactor power operate within acceptable temperature limits and ensure the operation safety of the space reactor power. In future research, the dynamic characteristics of the reactor will be considered to study the influence of the space thermal environment on the cold startup process of the space reactor. Whether the reactor is successfully started will be the key of the whole power system of the space reactor.